Revisión y balance del corpus de téseras celtibéricas (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Review and assessment from the historical, paleo-epigraphic and linguistic point of view of the documents considered, to the present, celtiberian tesserae.
Keywords: Epigraphy; tesserae; celtiberian language